2015
DOI: 10.1111/mcn.12192
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose RUTF protocol and improved service delivery lead to good programme outcomes in the treatment of uncomplicated SAM: a programme report from Myanmar

Abstract: The treatment of uncomplicated severe acute malnutrition (SAM) requires substantial amounts of ready-to-use therapeutic food (RUTF). In 2009, Action Contre la Faim anticipated a shortfall of RUTF for their nutrition programme in Myanmar. A low-dose RUTF protocol to treat children with uncomplicated SAM was adopted. In this protocol, RUTF was dosed according to beneficiary's body weight, until the child reached a Weight-for-Height z-score of ≥−3 and mid-upper arm circumference ≥110 mm. From this point, the chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 10 publications
(9 reference statements)
6
28
1
Order By: Relevance
“…This is similar to that reported elsewhere [ 22 , 26 , 27 ]. In our study, it was also found that the length of stay for those recovered children was 7 weeks / 49 days which is lower than the study in Gedaref, Northern Sudan which showed 60 days [ 23 ], 54 days in Burkina Faso [ 22 ] and higher than 42 days reported from Myanmar [ 27 ]. These differences might be attributed to the different discharge criteria used in the different settings, which can influence the length of stay.…”
Section: Discussionsupporting
confidence: 93%
“…This is similar to that reported elsewhere [ 22 , 26 , 27 ]. In our study, it was also found that the length of stay for those recovered children was 7 weeks / 49 days which is lower than the study in Gedaref, Northern Sudan which showed 60 days [ 23 ], 54 days in Burkina Faso [ 22 ] and higher than 42 days reported from Myanmar [ 27 ]. These differences might be attributed to the different discharge criteria used in the different settings, which can influence the length of stay.…”
Section: Discussionsupporting
confidence: 93%
“…This finding was in line with Gebremichael et al, who showed that weight at recruitment lower than the mean increased nutritional recovery time for severely malnourished children [26]. James et al also found that WHZ less than − 3.5 was associated with lower odds for recovery among children in Myanmar [27]. Similarly, in an inpatient program of non-edematous children aged 6-59 months in Uganda, low WHZ at admission was a significant risk factor for mortality [28].…”
Section: Discussionsupporting
confidence: 74%
“…While many studies used WHO 2006 reference standards to define moderate and severe stunting and wasting (labelled ‘WHO’ in Table ), others used the National Center for Health Statistics (NCHS)/WHO international growth reference standards (labelled NCHS in Table ) . Wasting (WFH) was used as an outcome in 15 studies , stunting (HFA) in five studies , underweight (WFA) in five studies and MUAC in five studies . Four studies described weight gain and one described linear growth .…”
Section: Resultsmentioning
confidence: 99%
“…Recovery rates of 67–81% were seen in two studies examining take‐home selective supplementary feeding for those with mild or moderate malnutrition using millet gruel and corn–soy blend, respectively . Rates of over 90% were seen in therapeutic feeding studies using RUTF in those with severe malnutrition . However, recovery rates were defined differently in each study: Nielsen used MUAC >130 mm, Vautier used >85% WFH, James used 15% weight gain or MUAC >110 mm and Amthor used WFH >100% reference standard.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation